1974
DOI: 10.1002/neu.480050505
|View full text |Cite
|
Sign up to set email alerts
|

Feedback cue and switching characteristics

Abstract: Asexual reproduction (fissioning) in planarians is controlled by group size; increased group size suppresses fissioning, isolation releases it. This effect is mediated through the brain; social stimulation from cohorts causes the brain to inhibit the segmental plexus fissioning system from initiating the events of fissioning. Experiments were conducted to elucidate 1) the stimulus cue conveying information regarding cohort number and 2) the switching characteristics of the control system. The results of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1974
1974
1987
1987

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Or why, in isolated worms, should ablation of the cephalic margins yield any further increase in fissioning? A previous study (Best et al, 1974) indicated some suppression of fissioning by nonspecific background stimulation of intact isolates which, although not large in comparison to social stimulation effects, was significant. This finding, taken altogether with the fact that our marginal ablation removes most, but not all, neural cilia of the cephalic surface, permits one to answer the two questions posed a t the beginning of this paragraph.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Or why, in isolated worms, should ablation of the cephalic margins yield any further increase in fissioning? A previous study (Best et al, 1974) indicated some suppression of fissioning by nonspecific background stimulation of intact isolates which, although not large in comparison to social stimulation effects, was significant. This finding, taken altogether with the fact that our marginal ablation removes most, but not all, neural cilia of the cephalic surface, permits one to answer the two questions posed a t the beginning of this paragraph.…”
Section: Discussionmentioning
confidence: 81%
“…The inhibitory effect of the brain becomes attenuated with distance along the axis of the worm; under comparable conditions, long worms are more likely to fission than short ones. The "switching" characteristics are also suggestive of those to be anticipated from a rieurohumoral meclhanism; release of fissioning, following isolation, is sluggish but the inhibition of fissioning, following regrouping, is rapid (Best et al, 1974).…”
Section: Pigon M O R I T a A N D B E S Tmentioning
confidence: 94%
See 2 more Smart Citations